Antimicrobial effect of benzbromarone combined with colistin against multidrug-resistant bacteria - Wang, Feng; Li, Hongjun; Bao, Xiaoqiang (Frontiers in Medicine, 2025)
IntroductionDrug-resistant respiratory pathogens in COPD patients pose a major therapeutic challenge. Colistin is a last-resort treatment for drug-resistant infections. But emerging resistance and hepatorenal toxicity limit its use, which highlights the need for combination strategies to improve its efficacy and safety. This study investigated the antibacterial effect of the combination of benzbromarone and colistin against drug-resistant pathogens associated with COPD.Methods and ResultsIn this study, MIC determination experiments revealed that respiratory pathogens from COPD patients exhibited high resistance rates to several conventional antibiotics. Furthermore, the checkerboard assay showed that benzbromarone alone had no antibacterial effect but markedly lowered the MIC of colistin, with all FICI values <0.5. Further growth curve and time kill curve analysis showed that colistin combination with benzbromarone significantly enhanced bacterial growth inhibition and exerted bactericidal activity. Additionally, the antibacterial mechanism showed that colistin combined with benzbromarone synergistically enhanced bacterial membrane damage, promoted ROS accumulation, and inhibited ATP production, thereby exerting stronger bactericidal effects. Moreover, validation using the Galleria mellonella larval infection model demonstrated that the benzbromarone-colistin combination provided effective protection against infections caused by multidrug-resistant Gram-negative bacteria, with larval survival rates reaching up to 70%, which was significantly higher than that observed with monotherapy.DiscussionThis study revealed that benzbromarone enhanced the antibacterial activity of colistin against COPD-associated drug-resistant pathogens, exhibiting a significant synergistic effect while effectively reducing the required colistin dosage. These findings provide a promising alternative approach for antimicrobial therapy in drug-resistant COPD infections and contribute to the exploration of new antibacterial applications for non-antibiotic drugs.